84.4k views
2 votes
Helpppppppppppppppppppppppppp
5 and 8

Helpppppppppppppppppppppppppp 5 and 8-example-1
User Kgrittn
by
4.8k points

1 Answer

5 votes

Answer:

5. -3, -2/3

Explanation:

5.

6x-4y=18

-x-6y=7 multiply this equation by 6 both sides

6x-4y=18

-6x-36y=42 add both equations

-4y-36y=18+42 combine like terms

-40y=60 so y = -4/6= -2/3

subtitute y=-2/3 in -x-6y=7

-x-6*(-2)/3=7 solve

-x+4=7 subtract 4 from both sides

-x=7-4

x= -3

8.

substitute y=4x+5 in to the second equation

12x-3(4x+5)=9

12x-12x-15=9

-15=9 is never true so the equation has no solutions

User Rafael Angarita
by
5.5k points